Kinerja Biosorben Cangkang Telur sebagai Pengadsorbsi Logam Berat Cr pada Limbah Industri - Syahril Makosim; mohamad haifan; Eka Indra Setiaman (Institut Teknologi Indonesia, 2020)
In industrial processing, side products are produced in the form of liquid waste containing heavy metals, including Cr (III) which can have a negative impact on the environment. Some egg shell characteristics containing high concentrations of CaCO3 and have a natural pore structure can be used as adsorbers (biosorbents) of heavy metals produced by the processing industry. The purpose of this study was to obtain the optimum conditions of absorption (adsorption) of Cr (III) metals carried out by egg shell biosorbents. The research method was carried out experimentally which included the preparation of egg shell waste biosorbents, determining the optimum time, as much as 1.0 gram of eggshell biorsorbent was put into 25 ml of heavy metal waste solution with a concentration of 50 ppm, then adsorption was carried out with time variations of 5, 10, 20 , 30, 40, 50, 60 and 120 minutes. Variation of Cr concentration were 50,0 ppm; 100,0 ppm, 150,0 ppm; 200,0 ppm; 250,0 ppm; 300,0 ppm; 350,0 ppm, 400,0 ppm; 450,0 ppm; 500,0 ppm; dan 1000 ppm. After that the mixture is filtered and the filtrate is read on the Atomic Absorption Spectrophotometer (AAS) to find out the maximum adsorption. The results showed the optimum conditions of adsorption of Cr (III) metals obtained an optimum time of 40 minutes with an absorption capacity of 1242.46 µg Cr (III) / g biosorbent, and optimum concentration with optimum treatment time and weight at 200 ppm with an absorption capacity of 4984 , 99 µg Cr (III)/g biosorbent. The adsorption isotherm adopts the Freundlich isotherm or physically (physical) type, because the linearity of the Freundlich isotherm obtained from the calculation results is R2 = 0.7312 or 73.12% higher than the Langmuir isotherm ie R2 = 0.0335 or 3.35%. Keyword : Cr (III) heavy metal, eggshell biosorbent, optimum adsorption conditions